1957
DOI: 10.1037/h0044108
|View full text |Cite
|
Sign up to set email alerts
|

Differences in perceptual and cognitive behavior as a function of experience type.

Abstract: The proposition that differences in experience type on the Rorschach reflect certain trends in personality functioning has been a common assumption in clinical practice. In a previous paper (3), it was pointed out that one way of conceptualizing the experience type is in terms of the person's use of internal and external stimulus factors. The introversive person utilizes internal stimulus factors to a greater degree in that he invokes aspects of the stimulus situation more proximal to himself, while the extrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1960
1960
1983
1983

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…The present data are not adequate to allow for further exploration of these conjectures regarding sex differences. Nevertheless, the authors at least can confirm the findings of Bieri et al (1958) and Bieri and Messerley (1957) that sex differences in regard to different perceptualcognitive tasks are profound and seem to have different meanings for each sex. Any work that concerns fantasy activity or attentional processes must make allowances for sex differences, and generalizations being derived from such work should be made with caution.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The present data are not adequate to allow for further exploration of these conjectures regarding sex differences. Nevertheless, the authors at least can confirm the findings of Bieri et al (1958) and Bieri and Messerley (1957) that sex differences in regard to different perceptualcognitive tasks are profound and seem to have different meanings for each sex. Any work that concerns fantasy activity or attentional processes must make allowances for sex differences, and generalizations being derived from such work should be made with caution.…”
Section: Resultssupporting
confidence: 55%
“…For one, the Nyman study used only male 5s, while Antrobus et al used male and female 5s. Bieri and Messerley (1957) and Bieri, Bradburn, and Galinsky (1958) found that M production correlates differently and at times, in the opposite direction, with other cognitive variables in male and female samples. In short, M production does not necessarily predict to the same consequences for both sexes.…”
mentioning
confidence: 96%
“…Conceptual differentiation in categorizing can be conceived of as an aspect of cognitive complexity. It is therefore necessary to consider relations between this dimension of individual consistencies and that inferred from responses to the role construct repertory tests developed on the basis of Kelly's (1955) work and used by a number of investigators to assess cognitive "complexity-simplicity" (see, e.g., Bieri, 1955;Bieri & Blacker, 1956a, 1956bBieri & Messerley, 1957;Dopp, 1960;Leventhal, McGaughran, & Moran, 1959;Lundy & Berkowitz, 1957). Kelly (1955) emphasizes the importance of contrast in concept formation.…”
Section: Conceptual Differentiation and "Cognitive Complexity"mentioning
confidence: 99%
“…Rorschach's distinction between objective and subjective orientation is the crux of Jung's theory, and descriptions of the two Rorschach "experience types" are remarkably like Jung's characterizations of the extravert and introvert. Moreover, evidence from several studies indicates that some of the empirically found differences between extratensive and introversive subjects correspond to hypothesized or observed differences between extraverts and introverts (Bash, 1955;Bieri & Messerley, 1957;Mann, 1956;Palmer, 1957;Singer & Spohn, 1954).…”
Section: Analyses Of Protective Testsmentioning
confidence: 89%